Immunomodulatory Effect of Virgin Coconut Oil in Wistar Rats Infected with Staphylococcus aureus - Desy Cahya Widianingrum; Siti Isrina Oktavia Salasia (Jurnal Ilmu Ternak dan Veteriner, 2021)
Virgin coconut oil (VCO) contains bioactive that induce immunity against infectious diseases. This study aim to determine the immunomodulatory effects of VCO based on the activity of superoxide dismutase (SOD), lymphocyte proliferation, and histopathological examination in liver and kidney of rats infected with Staphylococcus aureus. The VCO was given intragastrically to rats with a dose of 250 µL for one week. The rats were infected with S. aureus at 5x102 bacterial cells intraperitoneally. Twenty (20) female Wistar rats of one month old were divided into four groups. The negative control group (C-): without treatment, AV group: infected with S. aureus followed by VCO treatment; VA group: pretreated with VCO followed by S. aureus infection, and positive control group (C+): were infected with S. aureus without VCO. All rats were euthanized and necropsied based on the animal ethic standard. Plasma samples were taken to evaluate SOD activity, and lymphocytes were isolated from the spleen to determine their proliferative ability. Livers and kidneys were collected for a histopathology examination. Results showed that the VA group had the highest SOD activity on the 4th week (41.50 ± 3.56 %) and lymphocyte proliferation (0.3018) compared to all treatments, indicating immunomodulatory effects of VCO. Liver of treatments group showed leucocytes infiltration, no hemorrhages (VA); the hepatocytes with normal cells (VA). Kidney of treatments group showed leucocytes infiltration (AV); normal epithelial glomerulus and tubulus cells, still found hemorrhage (VA). These studies indicated that VCO has a potential role as an immunomodulator, hepatoprotectant, and nephroprotectant.